Maja Fruit Extracts Inhibit Escherichia coli, Reduce Fly Larvae Population, and Ammonia Emission of Chicken Excreta - Syaefullah, B. L.; Erwanto, Y.; Wihandoyo; Muhlisin; Prasetyo, R. A.; Kurniawati, N.; Fitriyanto, N. A. (Tropical Animal Science Journal, 2020)
The characteristic of chicken excreta has a very potential as a breeding media for flies and is known for causing odorous pollutants (NH3 emission) from undigested protein and the activities of urease microorganisms. This study is focused on extracting Maja fruit, to quantify marmelosin from different fruit conditions using HPLC, and to determine the biological activity for handling the chicken excreta problems. In this study, the Kirby-Bauer Test was used to observe the antibacterial activity of marmelosin, the NH3 trapping method was used to determine ammonia emission, and the larvae population was determined by the Fly-Grill method. Marmelosin contents in MFE from immature, mature, and fermented fruit condition were 108.65 μg/g; 65.83 μg/g, and 23.02 μg/g, respectively. The increasing level of marmelosin addition to 50, 100, 150, and 200 μg/mL caused the higher diameter of inhibition zone against E. coli (p<0.05), which were 2.50, 2.90, 5.06, and 7.27 mm, respectively. The increasing level of MFE addition at 5, 7.5, and 10% (v/v) showed a higher inhibition effect on the NH3 emission from the excreta. The addition of MFE up to 10% (v/v) had no significant effect on the total larvae population of flies that existed in the excreta. It can be concluded that the highest marmelosin content was confirmed in the immature fruit condition. The highest antibacterial activity of marmelosin from MFE was shown at the concentration of 200 µg/mL. The application of 10% (v/v) MFE to the excreta gave the highest inhibition of NH3 emission and minimized the average larvae population of flies.